2012
DOI: 10.1111/j.1365-2672.2012.05372.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial signalling molecule indole attenuates the virulence of the fungal pathogen Candida albicans

Abstract: Aims: Indole is a signalling molecule, produced by a number of Gram-positive and Gram-negative bacteria both in nature as well as clinical environments. Here, we explored the effect of bacterial indole and one of its main derivatives on the virulence of the fungal pathogen Candida albicans. Methods and Results: We found that indole and its derivate indole-3-acetonitrile (IAN) did not affect the viability of C. albicans. Interestingly, indole and IAN repressed C. albicans biofilm formation as well as the attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…For example, indole inhibits the attachment of the fungal pathogen Candida albicans to intestinal epithelial HT-29 cells [56] and reduces the production of the virulence factor staphyloxanthin in Staphylococcus aureus [57]; both of these studies demonstrated virulence reduction in a Caenorhabditis elegans model [56,57]. Indole also inhibits cyanobacterial blooms caused by the formation of periphyton biofilms [58], induces biofilm formation by rhizospheric Burkholderia unamae [59], and delays predation by Bdellovibrio bacteriovorus [60].…”
Section: Antivirulence Activities Of Indoles Against Non-indole-produmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, indole inhibits the attachment of the fungal pathogen Candida albicans to intestinal epithelial HT-29 cells [56] and reduces the production of the virulence factor staphyloxanthin in Staphylococcus aureus [57]; both of these studies demonstrated virulence reduction in a Caenorhabditis elegans model [56,57]. Indole also inhibits cyanobacterial blooms caused by the formation of periphyton biofilms [58], induces biofilm formation by rhizospheric Burkholderia unamae [59], and delays predation by Bdellovibrio bacteriovorus [60].…”
Section: Antivirulence Activities Of Indoles Against Non-indole-produmentioning
confidence: 96%
“…Hence, more potent, stable, non-toxic indole derivatives than indole have been proposed as potential antivirulence compounds. For example, plant-derived indolylacetonitrile reduces virulence factor production in P. aeruginosa, in which the compound is stable [42], indolylacetonitrile reduces the virulence of C. albicans more effectively than indole [56], 7-benzyloxyindole attenuates the virulence of S. aureus more than indole [57], and 6-chloroindole inhibits the growth of, and biofilm formation by, algal Cylindrotheca sp. by inducing Ca 2+ efflux [66].…”
Section: Antivirulence Activities Of Indoles Against Non-indole-produmentioning
confidence: 99%
“…and Penicillium sp., produce indole derivatives that have been reported to inhibit C. albicans biofilm formation and hyphal development (Wang et al ., 2012; You et al ., 2013). Although relatively few reports are available to conclude, indole and indole‐3‐acetonitrile have been shown to suppress biofilm maturation by C. albicans (Jayant et al ., 2012; Oh et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, indole produced from just a few cells can protect a large population of E. coli against several antibiotics . Indole-regulated behaviours also extend to inter-species communication by affecting efflux-mediated multidrug resistance, flagella synthesis, virulence factor expression and host cell invasion by indole-non-producers like Salmonella enterica, Pseudomonas aeruginosa and even the yeast Candida albicans (Lee et al, 2009;Nikaido et al, 2011Nikaido et al, , 2012Oh et al, 2012;Raut et al, 2012). Finally, indole and other tryptophan-derived metabolites balance inflammation in the mammalian intestinal tract (Bansal et al, 2010;Keszthelyi et al, 2012;Nicholson et al, 2012) and strengthen the barrier function of epithelial tight junctions (Bansal et al, 2010;Keszthelyi et al, 2012;Nicholson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%